Systematic Literature Review: Transformasi Perilaku Konsumen di E- Commerce Terhadap Pengaruh Personalisasi AI, Kekhawatiran Privasi, dan Loyalitas Merek pada Generasi Z - Joanna Ciendy Inasa Putri; Mohammad Khusnu Milad (Jurnal Ilmiah Ekonomika & Sains, 2025)
The rapid advancement of artificial intelligence (AI) technology has significantly transformed how consumers interact with e-commerce platforms. Generation Z, as the most digitally engaged consumer segment, demonstrates a strong preference for personalized and seamless online shopping experiences. This study provides a comprehensive review of how AI-based recommendation systems shape Generation Z’s purchasing decisions by balancing personalization, privacy protection, and brand loyalty. Using a Systematic Literature Review (SLR) approach, this research compiles and interprets recent empirical findings from academic publications to identify emerging patterns, ethical challenges, and marketing strategies relevant to digital-native consumers. The findings indicate that AI-driven personalization enhances consumer engagement and strengthens brand relationships; however, privacy concerns remain a major barrier to building long-term trust. Therefore, e-commerce companies are encouraged to implement transparent and ethical data management policies to foster sustainable consumer loyalty among Generation Z.